Two new species of Mesoplecia (Insecta: Diptera: Protopleciidae) from the late Middle Jurassic of China - Lin, Xiuqin; Shih, Chungkun; Ren, Dong (Zootaxa, 2014)
Two new species of Mesoplecia Rohdendorf, 1938, M. plena sp. nov. and M. fastigata sp. nov., are described from the late Middle Jurassic Jiulongshan Formation of Daohugou, Inner Mongolia, China. Based on the emended generic diagnosis of Mesoplecia by Zhang in 2007, these two new species are assigned to Mesoplecia by a combination of the following five characters: (1) Head small; (2) Vein bRs not more than twice as long as dRs; (3) M1, M2 at least 5 times as long as dM1+2; (4) bM1+2 longer than dM1+2; and (5) Legs with coxae and femora thick. In addition, a key to Mesoplecia is provided.